Psychiatric experience with perpetrators - Lansen, Johan (Torture Journal, 2020)
Reprinted with permission from Journal of Medical Ethics, 17(Suppl), 55–57. doi: https:/doi.org/10.1136/jme.17.suppl.55 © 1991 BMJ Publishing Group Ltd & Institute of Medical Ethics. All rights reserved.